REDESAIN LOGO UNIT USAHA PUSAT KEGIATAN BELAJAR MASYARAKAT SUKA MAJU SEJAHTERA KOTA PADANG - SUMEMA, Dra. Zubaidah, M.Sn., Hendra Afriwan, S. Sn., M. Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2015)
The objective of this design is to redesign the logo of Pusat Kegiatan Belajar Masyarakat (PKBM) Suka Maju Sejahtera (SMS) of Padang, with an design that easy to remember, flexible, dynamic dan communicative. Analysis aprroach of this design is SWOT (Strength, Weakness, Opporunity, Treatment). Based on the analysis this logo used CASPER (contrast, alignment, simplicity, proximity, emphasis, repetition) rules standar, that rules has made legability, readibility and flexibility of the logo easily understood by its target audience. The redesign of this logo is the main design and it is aimed to support promotion media. Logo as visual identity has created product potitioning in the target audience mind. The redesign of this new logo helpes to develope community image about this business unit PKBM SMSKeyword: Redesign, Logo, PKBM, Suka Maju Sejahtera.